Simulation of TLD-700 (Lif; Mg, Ti) for Determination of Hp Equivalent Dose (10) on Radiation Workers (Gamma) with MCNPX Approach - Pradipta, Aisyah Dianing; Rianto, Sugeng; Bunawas, Bunawas (Natural B, 2017)
Radiation workers are compulsory to monitoring radiation dose for reduce the effects of ionizing radiation on the body. Government through similar BAPETEN maximum dose for radiation workers is 20 mSv/year. One of the personal monitoring tool that is widely used is the TLD-700 (specially for gamma radiation). The equivalent dose to the workers body to a depth of 10mm (Hp(10)) able to be predicted from a simulation approach MCNPX. To simulation needed input model of geometry which adapted to the geometry experiments. The simulation results at the source position vertical to the dose rate is obtained 8,565mSv/h, which shows a difference of 1.5% on the results of the experiment, so the Hp(10) dose can be determined. This experiment able to simulated for contamination source 137Cs on the floor position unable to be done experimentely contamination source. Estimation through simulation, the dose rate on the floor at 14.920 mSv/h. The results showed the difference of dose rate through dose rate 75% vertical source larger than the vertical direction. According to the result need to be calibration TLD-700 for the source position from the bottom. Because the greater the dose rate (from below), the greater the Hp(10) dose is received. With the result clear that considerable potential MCNPX used to estimate personal Hp(10) dose for radiation workers, specially in relation to the case of a radiation accident.